(untitled) (Biological Sciences - PJSIR, 1996)
A rapid, accurate and simple colorimetric method is proposed for the determination of melloquine in biological fluids and pharmaceutical dosage forms. The green complex (soluble in nitrobenzene) formed between melloquine and cobalt/thiocyanate reagent has absorption maximum at 625nm. The percentage recoveries of 98-10I% obtained in urine, plasma and serum and the limit of sensitivity of 0.1 ug/rnl showed that the method is applicable to the determination of metloquine in these biological tluids. The method also gave a percentage label strength of 98% for formulated mefloquine tablets and capsules.